THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND LEADERSHIP STYLE TO EMPLOYMENT MOTIVATION IN PT. ABL - Sasongko, Dwi Anggoro Sukmo; Tampubolon, Emma Tampubolon; Sinaga, Sautman Sinaga (Universitas Kristen Indonesia, 2018)
This study aims to determine: 1) the relationship between organizational culture with employee motivation in PT. BRI Life Insurance Head Office, 2) relationship between leadership style with employee motivation at PT. BRI Life Insurance Head Office, 3) relationship between organizational culture and leadership style to employee work motivation in PT. BRI Life Insurance Head Office (PT.ABL). Based on the research results can be obtained conclusion as follows: 1) there is a significant relationship between organizational culture with employee motivation in PT. BRI Life Insurance Head Office. This is evidenced by the value of t count (6,931)> ttable (1,993), 2) there is a significant relationship between leadership style with employee motivation at PT. BRI Life Insurance Head Office. This is evidenced by the tcount (7,135)> ttable (1,993). Of the two most dominant independent variables affecting work motivation is the leadership style. This is indicated by the greater contribution of leadership style (41.1%) than the contribution of organizational culture (39.7%); 3) there is a significant relationship between organizational culture and leadership style with employee work motivation in PT. BRI Life Insurance Head Office. This is evidenced by the value of Fcount (58.973)> Ftable (3.124) Keywords: Organizational Culture, Leadership Style, Employee Motivation